Fourteenth Collegium Ramazzini statement call for worldwide reduction in exposure to lead - Office, Editorial (European Journal of Oncology and Environmental Health, 2008)
Lead is a pervasive occupational and environmental hazard. Despite great progress in reducing lead exposure, lead toxicity remains a major health problem, and lead use is increasing worldwide. Lead poses serious hazards to workers’ health and also to the health of infants and children...